Capillary Electrophoresis with Diode Array Detection for the Quantification of Triptorelin and Lanreotide in Pharmaceutical Quality Control: Development, Validation, Greenness and Practicality Evaluation - Stefanik O.; Mikus P.; Piestansky J. (European Pharmaceutical Journal)
Capillary electrophoresis (CE)-based methods hold significant potential for routine use in pharmaceutical quality control (QC) laboratories. Therefore, this study aimed to develop a novel, green, and simple hydrodynamically open-system capillary zone electrophoresis method with diode-array detection (CZE-DAD) for the simultaneous analysis of lanreotide and triptorelin in a single electrophoretic run and to objectively evaluate the analytical technique’s greenness and practicality for application in the pharmaceutical QC settings.